(untitled) - Harter, James (New York, 1998)
Incorporating use of SI Units throughout the text in each of the application chapters, this work emphasizes key terminology through end-of-chapter glossaries that present key terms for review. Calculator uses are flagged in the margins.
Keywords: Electronics; Mathematics